For dramatic construction in the collection (In This Black Garden) by the poet Abdel Zahra Zaki - Dr. duea Ibrahim Rashid Al-Obaidi (Journal of College of Education, 2024)
The openness of the poetic text and its intersection with literary genres gave the poetic texts an expressive aesthetic, with a dramatic language that expresses the reality that the poet lives. Abdel Zahra Zaki presented his collection (In This Black Garden) with a dramatic structure, using narrative mechanisms, taking advantage of the interplay between genres, to draw a narrative picture that mimics the characters. Events in a narrative and creative space and in an suggestive language